FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA DALAM BERKARIR SEBAGAI KONSULTAN PAJAK - Utami, Putri; Rispantyo, Rispantyo (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
Interest is a human tendency regarding things that attract their attention which encourages or motivates people to do or choose things they find interesting after various considerations. This research was conducted with the aim of finding out what factors influence accounting students attract in choosing a job as a tax consultant. The factors measured include: perception, tax knowledge, job market considerations and financial rewards. This research uses a survey method using a questionnaire distributed to accounting students from private universities in the city of Surakarta class of 2020. The sample in this study was 68 students calculated using the Slovin Formula. This research analysis uses descriptive statistical tests, classical assumption tests and hypothesis tests using the SPSS Version 25 application. The research results show that perception, tax knowledge, job market considerations and financial prices had a partially positive and significant effect on students interest in pursuing a job as a tax consultant.